Effect of Storage on Seed Viability and Germination of Certain Leguminous Trees - Arya, Chitra; Arya, Arun (Indian Forester, 2006)
Effect of storage on viability of 23 leguminous taxa of Gujarat forest at different temperatures was studied for six years i.e. from 1997- 2002. Seed viability was calculated after performing tetrazolium test and seed germinability was tested using Blotter method. Percentage viability was more for seeds of A. nilotica and C. fistula after 6 years at room temperature than seeds of A.lebbek, C. fistula C. javanica, C. siamea, D. regia, P. dulce, and P. juliflora. It varied from species to species even under the same storage conditions. Seed health at low temperature storage condition and prevailing relative humidity is responsible for enhanced viability and more germinability of seeds.